PENGARUH MANAJEMEN KELAS TERHADAP MOTIVASI BELAJAR SISWA DI SMK NEGERI 1 KOTA JAMBI - Richi Purnawan; Yusdi Anra; K. A. Rahman (Jurnal Ilmiah Dikdaya, 2018)
This research’s aims to describe about class management and student’s motivation to learn and also to find out if there is an influence of management class on student’s motivation to learn in SMK Negeri 1 Jambi City School Year 2018/2019. This research’s take place in SMK Negeri 1 Jambi City on July 2018 with sample of 52 respondens. Research data obtained by distributing questionnaiers to students. After the questionnaiers is filled and returned to the researcher, then the researcher analyzed the data with descriptive statistics and interference statistics with data analytical techniques simple regression. The result showed that the description of class management has 73,32% quality including good catergory. Then, th decription of student’s motivation to learn has 73,25% quality including high category. While, the influence of class management on student’s motivation’s learn has 28,5% with regression’s equal Y = 47.007 + 0,462 X this is based on determination coefficient, earned value R square as much as 0,285. The result of this research is to recommend the teachers to increase the ability of management class, then the headmaster should give the training to the teachers about class management, and also to students should discussed with teachers and homeroom teacher about class management.Keywords: Class Management, Motivation To Learn